ASSESSMENTS OF AUTOANTIBODY AND CYTOKINE CONTENTS IN TEENAGERS OF INDUSTRIAL CENTERS SCREENING EXAMINATION - L. B. Masnaviyeva; I. V. Kudayeva (Acta Biomedica Scientifica)
270 teenagers without acute inflammation signs at the moment of the examination living in the industrial centers of Eastern Siberia have been examined. The declinations from the reference levels of the relative autoantibody content to native DNA were found to observe in 23.5 %, to β2-glycoprotein I — in 47.0 %, to Ig G Fc-fragment— in 31.3 % of the cases. It was revealed that gyperimmunoresponsiveness of the autoantibodies to β2- glycoprotein. I may be followed by the increase in the concentration of γ-interferon. The fluctuations of the of interleukin 2 and 10 contents and α-interferon in the dependence on the immunoresponsiveness were found to be in the range of the reference values.